Education for sustainability of water resources - Krasilchik, Myriam; de Carvalho, Luiz Marcelo [UNESP]; Silva, Rosana Louro Ferreira (Springer Nature, 2016)
In this paper we present an analysis of fundamental aspects to contextualize the environmental education as an essential component to discuss water resources sustainability. First, we point out historical factors concerning the establishment of Environmental Education in Brazil, underscoring water resources in projects, programs and public policies. After that, we discuss social and institutional factors associated with water resources and their interface with environmental education, in reference to the National Policy and Plan for Water Resources (Política e Plano Nacional dos Recursos Hídricos), the National Policy for Environmental Education (Política Nacional de Educação Ambiental) and the National Curricular Guidelines (Parâmetros Curriculares Nacionais). Within the academic context, we present quantitative and qualitative data from research in the field of environmental education, particularly research projects that focus on water resources, indicating their trends and perspectives in knowledge production on a national level. Finally, we suggest perspectives for a critical environmental education and highlight ways under which the approach underlying pedagogical practices and textbooks can be identified, mainly concerning the core concept of river basins that allows a systemic analysis of problems associated with water resources. These suggestions are based on the premises that environmental education may be an important tool to empower participatory management and knowledge exchange, and that this systemic and interdisciplinary approach should be a consistent component of pre-service and inservice teacher education programs.
Keywords: Environmental education sustainable development; Holistic approach; Research and critical reflection; Water sustainability